PENGEMBANGAN MANAJEMEN LAPAK USAHA OBYEK WISATA PANTAI BAHTERA ALAM KECAMATAN MEDANG KAMPAI - Fitra, Fitra; Arif, M; Azmi, Azmi; Mesra, Trisna; Melliana, Melliana (Komunitas Manajemen Kompetitif, 2022)
The development of coastal tourism objects can be a leading natural tourism in Dumai City. Medang Kapai sub-district, one of the sub-districts in Dumai City which is designated as a tourist area, has 7 beach attractions, namely: Puak Beach, Aulia Beach, Koneng Beach, Pulai Pungguk Beach, Bahtera Alam Beach, Lagenda Beach, and Panorama Beach. Bahtera Alam Beach as a tourist attraction that has existed since 2018. The results of interviews and surveys in the field found that the beach was not as busy as other beaches due to its development that had not been maximized by the management agency. Therefore, the PKM STT Dumai team carried out activities that helped local residents to increase the attractiveness of Bahtera Alam Beach which has a sandy coastline and is quite wide as far as the eye can see. Improving stall management and adding more attractive tourist spots.